Teaching Physics in Real-Life Contexts: The Beirut Explosion - Hernandez-Silva, C; Pino-Rozas, M (Institute of Physics, 2023)
Teaching physics in real-life contexts continues to be a challenge for teachers at different educational levels. In this article, three context-rich problems are proposed to be implemented in the classroom for higher education, using the explosion that occurred in Beirut as a case study. These problems require the search and analysis of real data, integrating technologies as tools to learn physics. In particular, the analysis of images, videos, maps and audio recordings is suggested. The proposed activities are designed to promote active learning of classical mechanics subjects and the development of collaborative skills. The results of each problem allow a discussion based on scientific evidence in the classroom. © 2023 IOP Publishing Ltd.